Comparison of HCl and H2SO4 for the acid activation of a cameroonian smectite soil clay: palm oil discolouration and landfill leachate treatment. Issue 12 (December 2019) - Ndé, H. Soh; Tamfuh, P. Azinwi; Clet, G.; Vieillard, J.; Mbognou, M. Tsaffo; Woumfo, E. Djoufac
Abstract: Vertisols occupy approximately 1, 200, 000 ha in Northern Cameroon. Their richness in smectites allows for the production of "bleaching earths" necessary for refining palm oil, and their effluent is used for leachate treatment. In the present work, two mineral acids (HCl and H2 SO4 ) were compared, and the most efficient acid with the lowest cost was determined for use in industrial applications. Under similar experimental conditions (ratio of acid solution/clay mass = 5/1, temperature = 97 °C, stirring time = 4 h), the quantity of cations (Fe 2+, Fe 3+, Al 3+ ) solubilised during acid activation, palm oil discolouration rate by each activated sample and the financial cost of 5 L of acid solution that is required for the acid activation of one kilogram of smectite clay were compared. It was found that 2N H2 SO4 was more efficient than 1N HCl and 1N H2 SO4, considering palm oil bleaching efficiency and cost. The filtrate collected after the acid activation of vertisols was rich in H + (2.04.10 −1 M), Fe 2+ (2.8.10 −3 M), Fe 3+ (4.2.10 −2 M) and Al 3+ (9.2.10 −2 M) ions. One gram of smectite clay material produced 9 mL of this filtrate that was used for the treatment of leachate from a controlled landfill. The leachate colour decreased from 4262 to 285 PtCo units, while the corresponding chemical oxygen demand (COD) decreased from 802 to 128 mg/L. Thus, the most effective acid for industrial bleaching earth production from vertisol is 2N H2 SO4 acid. Abstract : Environmental science; Materials chemistry; Smectite; Vertisol; Acid activation; Palm oil; Filtrate; Leachate treatment.